Gambaran Tingkat Kecemasan Ibu Hamil Primigravida Trimester III di Klinik Bersalin Sutra Minahasa Selatan - Maki, Frincia P.; Pali, Cicilia; Opod, Hendri (eBiomedik, 2018)
Abstract: Anxiety during pregnancy is often found among primigravidas, especially in the third trimester. Psychological disorders during pregnancy is associated with the occurrence of uterin artery resistance that might cause stunted fetal growth, premature birth, higher risk of premature baby, and even miscarriage. This study was aimed to obtain the anxiety level of third semester primigravidas at the South Minahasa Sutra Clinic. This was a descriptive study with a cross-sectional design. Hamilton Anxiety Rating Scale was used to obtain the level of anxiety. Respondents were all third semester primigravidas who visited the Sutra Clinic in the period of September to November 2018. The results showed that there were 32 respondents in this study. The anxiety levels of respondents were as follows: moderate anxiety in 14 respondents (43.8%), severe anxiety in 10 respondents (31.3%), and mild anxiety in 6 respondents (18.8%). There were 2 respondents (6.3%) who did not have anxiety. Conclusion: In the Sutra Clinic, the most common anxiety among the third semester primigravidas was moderate anxiety, followed by severe anxiety and mild anxiety.Keywords: third semester primigravidas, anxiety, Hamilton Anxiety Rating ScaleÂ Abstrak: Kecemasan selama kehamilan sering ditemukan pada ibu hamil primigravida, terutama pada trimester ketiga. Gangguan psikologis selama kehamilan berhubungan dengan terjadinya resistensi pada arteri uterin yang menyebabkan pertumbuhan janin terhambat, kelahiran sebelum waktunya, risiko melahirkan bayi prematur, bahkan sampai keguguran. Penelitian ini bertujuan untuk mendapatkan gambaran tingkat kecemasan ibu hamil primigravida trimester III di Klinik Sutra Minahasa Selatan. Jenis penelitian ialah deskriptif dengan desain potong lintang. Hamilton Anxiety Rating Scale digunakan untuk mengukur tingkat kecemasan. Responden penelitian ialah seluruh ibu hamil primigravida trimester III yang berkunjung ke Klinik Sutra pada periode September sampai November 2018. Hasil penelitian mendapatkan sebanyak 32 responden. Tingkat kecemasan pada responden ialah kecemasan sedang sebanyak 14 responden (43,8%), kecemasan berat 10 responden (31,3%), kecemasan ringan 6 responden (18,8%), dan tidak memiliki kecemasan 2 responden (6,3%). Simpulan: Tingkat kecemasan ibu hamil primigravida trimester III di Klinik Sutra yang terbanyak ialah kecemasan sedang, diikuti kecemasan berat dan kecemasan ringan.Kata kunci: ibu hamil primigravida trimester III, kecemasan, Hamilton Anxiety Rating Scale